Analisa Penjadwalan Proyek dengan Menggunakan Metode Line Of Balance (LOB) pada Proyek Pedestrian Jl. MH. Thamrin-Jl. Halim Perdana Kusuma - Ahmad Efendi; Annisa Dwiretnani; Ari Setiawan (Jurnal Talenta Sipil, 2022)
Choosing the appropriate method in project scheduling is an important thing to meet the needs in construction. Construction projects that have repetitive or repetitive work require a continuous and well-scheduled supply of labor, because the repetitive project work must be able to continue to progress without being delayed. Of the several project scheduling methods, line of balance (LoB) is more suitable for repetitive projects because line of balance (LoB) is a construction project scheduling method in the form of a line that represents one type of recurring activity package. LoB can be applied to repetitive projects. Repetitive projects are construction projects whose work is done repeatedly. The study objectives to be achieved are as follows: To find out the form of the Line of Balance (LoB) method network in the “Pedestrian JL. H. Thamrin - JL. Halim Perdana Kusuma". Knowing what is the optimal time to complete the project “Pedestrian JL. MH. Thamrin - JL. Halim Perdana Kusuma” using the Line of Balance (LoB) method. From the results of the analysis using the LOB method, the optimal project completion duration is 218 days, while the existing project time schedule is 240 days. So the calculation using the LOB method is 22 days faster than the existing time schedule.